2007
DOI: 10.1063/1.2793619
|View full text |Cite
|
Sign up to set email alerts
|

High bias voltage effect on spin-dependent conductivity and shot noise in carbon-doped Fe(001)∕MgO(001)∕Fe(001) magnetic tunnel junctions

Abstract: Low temperature (10K) high voltage bias dynamic conductivity (up to 2.7V) and shot noise (up to 1V) were studied in epitaxial Fe(100)/Fe-C/MgO(100)/Fe(100) magnetic tunnel junctions, as a function of the magnetic state. The junctions show large tunnel magnetoresistance (185% at 300K and 330% at 4K). Multiple sign inversion of the magnetoresistance is observed for bias polarity when the electrons scan the electronic structure of the bottom Fe-C interface. The shot-noise shows a Poissonian character. This demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 16 publications
8
50
0
Order By: Relevance
“…This dependence, as is evidenced in Figures 1b and 1c, is rather asymmetric being the inversion of the noise asymmetry linked to the TMR inversion point (see vertical dotted line in Fig.2.) We note that in general for the A-MTJs, both conductance and 1/f noise level appeared to be much more stable to the applied external electric field above 10 6 V/cm, in agreement with our recent findings for carbon-doped epitaxial Fe/MgO/Fe with large MgO barriers [19].…”
supporting
confidence: 80%
“…This dependence, as is evidenced in Figures 1b and 1c, is rather asymmetric being the inversion of the noise asymmetry linked to the TMR inversion point (see vertical dotted line in Fig.2.) We note that in general for the A-MTJs, both conductance and 1/f noise level appeared to be much more stable to the applied external electric field above 10 6 V/cm, in agreement with our recent findings for carbon-doped epitaxial Fe/MgO/Fe with large MgO barriers [19].…”
supporting
confidence: 80%
“…The efforts aimed at understanding spin coherency and SN, limited up to now to MTJs, revealed suppressed SN with Al 2 O 3 barriers (0:7 < F < 1) due to sequential tunneling [17] and also in serial MTJ arrays [18]. As for MTJs with MgO barriers, full SN (F ¼ 1) independent of the magnetic state was observed in epitaxial Fe=MgO=Fe [19]. Then, the noise was examined for ultrathin (less than 1 nm) MgO barriers, where F ' 0:92 was observed in the parallel state [20,21].…”
mentioning
confidence: 99%
“…14,15 It has also been shown experimentally that the Fano factor in a single-barrier magnetic tunnel junction depends on magnetic configuration of the junction, and can be remarkably enhanced for the antiparallel alignment of the electrodes' magnetizations. [16][17][18][19][20] Even more possibilities have been found in double-barrier tunnel junctions with two ferromagnetic electrodes and one ferromagnetic central layer, 21,22 where one can distinguish four magnetic configurations corresponding to different alignments of the magnetic moments of all three magnetic layers. 23 It has also been shown that a simple model based on two well-separated spin channels for electronic transport cannot properly describe the experimental observations without taking into account spin-flip transitions.…”
Section: Introductionmentioning
confidence: 99%